Order of magnitude enhancement of inherently selective atomic layer deposition of zirconia on silicon without deposition on copper: The role of precursor. (January 2022) - Saha, Soumya; Jursich, Gregory; Phakatkar, Abhijit H.; Shokuhfar, Tolou; Takoudis, Christos G.
Abstract: Zirconia atomic layer deposition (ALD) using zirconium 2 -methyl 2 -butoxide (ZMB) and ethanol is reported for the first time. The process selectively deposits a uniform ZrO2 film on silicon with a high deposition rate (∼2 Å/cycle), without any deposition on copper at a relatively low temperature (200 °C) and up to at least 200 cycles. This is the largest thickness of inherently surface selective ZrO2 ALD ever reported (∼400 Å) and is at least 10 times more selective than that achieved using a similar deposition process but with a different precursor, tris (dimethylamino)cyclopentadienyl Zirconium (ZyALD™). The selectively deposited ZrO2 films were characterized using spectral ellipsometry, X-ray photoelectron spectroscopy, extended X-ray absorption fine structure spectroscopy (EXAFS), atomic force microscopy and energy dispersive spectroscopy obtained during scanning electron microscopy and scanning transmission electron microscopy. Surface characterization techniques employed here confirmed the chemical nature and topography of the deposited ZrO2, whereas EXAFS showed the ZrO2 to be amorphous on silicon having local bonding structure similar to that of ZrO2 deposited with ZyALD™ precursor. Graphical abstract: Image 1 Highlights: Zirconia atomic layer deposition (ALD) using zirconium 2-methyl 2-butoxide (ZMB) and ethanol is reported for the first time. Inherently selective Zirconia ALD on silicon and not on copper is demonstrated for the first time with the ZMB/Ethanol system. Use of X-ray absorption, electron microscopy, X-ray photoelectron spectroscopy, atomic force microscopy and spectroellipsometry Inherently selective ALD Zirconia nanofilm thickness is ten- to fifteen-fold higher than that of any material reported to date.